FINANCIAL AND FIRM-SPECIFIC FACTORS AFFECTING CAPITAL STRUCTURE IN PHARMACEUTICAL COMPANIES: EVIDENCE FROM THE INDONESIAN STOCK EXCHANGE (2020-2023) - Lestari, Made Mitha; Gunadi, I Gusti Ngurah Bagus; Astiti, Ni Putu Yeni (EMAS, 2025)
The pharmaceutical sector plays a crucial role in health reform. Health issues are closely related to the availability of medicines. The pharmaceutical industry is part of the sector that plays an important role in the availability of various health products that support human quality of life. This study aims to explain the effect of liquidity, company size, profitability, and asset structure on the capital structure of pharmaceutical companies listed on the IDX from 2020 to 2023. The researchers used 11 pharmaceutical companies as the population, which were determined based on the purposive sampling method. The data analysis techniques used by the researchers included classical assumption tests, t-tests, descriptive statistics, F-tests, multiple linear regression analysis, and coefficient of determination tests. The results of the study show that profitability and company size do not significantly affect capital structure, while asset structure and liquidity in the capital structure of pharmaceutical companies listed on the IDX have a significant negative effect. Suggestions for further research include developing this study by adding other variables.